Employee Performance Based on Discipline, Workload, and Emotional Intelligence at the Dinas Sosial Kota Kupang - Jefirstson Richset Riwukore (Institute of Computer Science (IOCS), 2022)
The research objective was to determine the effect of discipline, workloads and emotional intelligence toward employee performance at Dinas Sosial Kota Kupang simultaneously and partially (quantitative). The sample in this research were all employees at Dinas Sosial Kota Kupang as many as 93 people. The data analysis technique used in this research is multiple linear regression testing, determination coefficient test, F test and t test. The research results obtained are: 1). Partial test (t test) which is performed prove that discipline has an effect to employee performance at Dinas Sosial Kota Kupang is t-value 5.536 > t-table 1.98638 and also a sig as many as 0,000 < 0,05; 2). Workloads affects to employee performance at Dinas Sosial Kota Kupang, where is t-value 33.683 > t-table 1,98638 an also a sig as many as 0,000 < 0,05; 3). Emotional intelligence affects toward employees performance at Dinas Sosial Kota Kupang, where is t-value 20.817 > t-table 1,98638 and also a sig as many as 0,000 < 0,05; 4). Discipline, workloads and emotional intelligence significant effect simultaneously to employee performance at Dinas Sosial Kota Kupang, where is F-value 459.956 > F-table 2,70 and also a sig as many as 0,000 < 0,05.